Skin, Inflammation and Sulfurous Waters: What is Known, What is Believed. (September 2013) - Carubbi, C.; Gobbi, G.; Bucci, G.; Gesi, M.; Vitale, M.; Mirandola, P.
One could argue that balneotherapy and mud therapy would have not lasted 2, 000 years or so If they were not effective. No doubt a long history cannot be taken per se as scientific proof of efficacy. Some empiricism is still present in the field: the concept of spa itself is quite confounding, whereas spring waters are used for leisure purposes but also for non-acute patient therapy and late phases of clinical recovery. These confounding elements ultimately feed the opinion of those who aprioristically reject any potential beneficial effect of balneotherapy: instead, it should at least generate questions that deserve scientific answers. Clinical practices sequentially integrating pharmacological therapy with those natural principles for which a sufficient scientific demonstration is available, would probably cut the costs of public health, generating widespread advantages for the community. Recently, it has become evident that mineral waters may have intrinsic pharmacological properties. Of the numerous salts dissolved in thermal waters that might show pharmacological properties, for certain hydrogen sulfide (H2 S) contained in sulfurous waters is the one that has obtained greater scientific attention, to which should be added the extensive scientific effort recently dedicated to H2 S as a cellular gasotransmitter, independently from its natural sources. Dermatology and cosmetics are among the most studied applications of sulfurous waters, around which, however, some empiricism still confounds opinions: we therefore considered that a state-of-the-art focus on this topic might be timely and useful for future studies.